Cancer Cytogenetics Methods and Protocols - Campbell, Lynda J.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2011)
Cytogenetic studies of malignancy have become an essential tool in the clinical management of cancer patients. Cancer Cytogenetics: Methods and Protocols presents eminently practical key cytogenetic and FISH techniques for every stage of diagnostic service. Experts in the field describe detailed cytogenetic analysis methods, fluorescence in situ hybridization and array methods currently being applied to investigate and diagnose different varieties of cancer. Written in the highly successful Methods in Molecular Biology™ series format, chapters contain introductions to their respective topics, lists of the necessary materials and reagents, and step-by-step, readily reproducible laboratory protocols. The authors of the various chapters have also provided extensive notes to guide individuals who are new to these methods through the pitfalls that bedevil all such testing.             Authoritative and accessible, Cancer Cytogenetics: Methods and Protocols serves as an ideal guide to scientists of all backgrounds, allowing them to either establish new techniques in their laboratories or find the different variations of standard methods helpful in improving their results.
Introduction -- Evolution of Cytogenetic Methods in the Study of Cancer -- Fluorescence In situ Hybridization Methods and Troubleshooting Applied to Fixed Cell Suspensions -- Chronic Myeloid Leukemia: Cytogenetic Methods and Applications for Diagnosis and Treatment -- Cytogenetic Analysis in Acute Myeloid Leukaemia -- Cytogenetics in Myelodysplastic Syndromes -- Cytogenetics of Myeloproliferative Disorders -- Acute Lymphoblastic Leukaemia -- Cytogenetics Methods in Chronic Lymphocytic Leukaemia (CLL) -- Genetic Abnormalities in Non-Hodgkin’s Lymphoma as Revealed by Conventional and Molecular Cytogenetics Methods of Analysis -- Metaphase Cytogenetic Techniques in Multiple Myeloma -- Detection of Chromosome Abnormalities using Cytoplasmic Immunoglobulin (cIg) Staining and FISH in Myeloma.- Cytogenetics of Solid Tumours -- Fluorescence In situ Hybridization on Formalin-fixed Paraffin-embedded Tissue Sections -- Use of M-FISH and M-BAND to Define Chromosome Abnormalities.- Utility of Array Comparative Genomic Hybridization in Cytogenetic Analysis -- Single Nucleotide Polymorphim Microarray Analysis of Genetic Alterations in Cancer -- Cytogenetic Analysis and Reporting.
Keywords: Cancer research; Cytogenetics; Cancer Research; Cytogenetics